Informal food chains and agrobiodiversity need strengthening—not weakening—to address food security amidst the COVID-19 crisis in South America - Zimmerer, Karl S.; Haan, Stef de (Springer, 2020)
The COVID-19 crisis is worsening food insecurity by undermining informal food chains. We focus on impacts involving the informal food chains that incorporate the resilience-enhancing biodiversity of food and agriculture known as agrobiodiversity. Our analysis addresses how informal food chains and agrobiodiversity are impacted by policies and interventions amidst COVID-19 disruptions. Our methodology relies on research in Peru with a focus on the cites and surrounding areas of Lima, Arequipa, Cusco, Huancayo, and Huánuco. We extend these insights to similar challenges and opportunities across western South America and other word regions. We utilize the four-part Agrobiodiversity Knowledge Framework to guide our examination of agrobiodiversity-related processes that interconnect governance, nutrition, agroecology, and the COVID-19 pandemic. Our results detail three links of informal food chains that are being disrupted and yet can offer resilience. These are food retailing, logistics and transportation, and seed systems. Utilization of the Agrobiodiversity Knowledge Framework cuts through highly complex issues to elaborate key food-security difficulties facing informal systems and how they can be strengthened to provide more resilience. We identify the specific roles of agrobiodiversity in resilience-enhancing processes that need strategic policy and program support. Results identify ways to augment the resilience of informal food chains using agrobiodiversity and the empowerment of social groups and organizations in urban food systems and rural communities. We conclude that the disruptions triggered by the global COVID-19 pandemic highlight the need to use agrobiodiversity as an instrument for resilience in informal food chains.